Are objective, official measures of disability reliable? - Per Johansson; Per Skedinger (Institute for Labour Market Policy Evaluation (IFAU), 2005)
The issue considered in this study is whether objective, official reports on disability status are reliable. While there is a rather large literature on the reliability of self-reported disability, evidence regarding objective data is scant. It seems to be a widely held view among researchers that, since individuals out of work are inclined to respond towards poor health, it would be best to have official data provided by the relevant administrative bodies. But we argue that such administrative data should be regarded with some suspicion, since the administrators also may have incentives to misreport. The empirical evidence, based on a large sample of Swedish jobseekers, suggests systematic misreporting by the Public Employment Service of objective, official disability measures due to incentives to exaggerate disability.
Keywords: I12; J28; J68; 330; Work disability; classification error; public employment service; Erwerbsunfähigkeit; Arbeitsvermittlung; Statistische Methode; Schweden; Statistischer Fehler